A hidden deadly venomous insect: First ecoepidemiological assessment and risk mapping of lonomism in Argentina - Casafús, Milena Gisela (2021)
Background: Envenomation by the South American Lonomia saturniid caterpillars, named lonomism, constitutes an emerging and somewhat neglected public health issue in Argentina and neighboring countries. Considering that there is an intricate relationship between environment and human health in such cases, this study aimed to analyze the eco-epidemiological profile of 40 accidents and 33 occurrences of Lonomia spp. in Misiones (Argentina) between January 2014 and May 2020. Methodology/Principal Findings: We described the eco-epidemiological variables and characterized the abiotic scenario of such cases. Additionally, we obtained a density map that shows the punctual intensity of Lonomia records throughout Misiones. Most of the accidents occurred in the Department of Guaraní and involved male victims younger than 20 years old. The accidental/occasional occurrence of Lonomia spp. (considering both adult and caterpillar stages together) was significantly higher in the rural area, whereas only adult specimens were found in urban areas. We determined that the presence of this insect in Misiones is positively related to higher temperatures and solar radiation, and larger precipitation and evapotranspiration throughout the year. Conclusion/Significance: This study represents an initial step towards the global understanding of lonomism as a public health problem in Argentina. It provides a map of the risk level for this envenomation in Misiones, which could help authorities address public health policy efforts to implement sustainable strategies for prevention and response to this threat in Northeastern Argentina and neighboring regions.